Mode II and Mode III Delamination of Carbon Fiber/Epoxy Composite Laminates Subjected to a Four-Point Bending Mechanism - Syed Abdullah, S.I.B.; Bokti, S.K.; Wong, K.J.; Johar, M.; Chong, W.W.F.; Dong, Roger (Elsevier BV, 2024)
Accurate determination of mode III interlaminar fracture toughness is paramount in composite materials due to its critical role in edge delamination, which nonetheless remains a significant challenge encountered. As such, this study focused on the investigation of mode II and III interlaminar fracture behavior of carbon fiber (CF)/epoxy composite laminates using four-end notched flexure (4ENF) tests and four-point bending plate (4PBP) tests, respectively. In particular, a cohesive zone model was employed for the simulation of the delamination process via finite element analysis (FEA). The mode II fracture toughness of CF/epoxy composites was determined to be 1.41 N/mm in experimental work. Additionally, experimental data in relation to force-displacement curves were in good agreement with numerical simulation results, which validated this simulation approach to successfully capture the mechanical response of composite laminates. In a similar manner, mode III delamination fracture toughness for CF/epoxy composites was numerically estimated to be 2.1 N/mm. Microscopic analysis indicated shear cusps were observed in both mode II and III specimens, as opposed to existing flakes discovered in mode III specimens only. Overall, this research enlightens a simple and effective way to estimate pure mode III fracture toughness and corresponding delamination behavior with respect to crack initiation and propagation.